(untitled) (Ameghiniana, 2014)
The taphonomic history of Tagelus plebeius (Lightfoot) at the Holocene estuary of río Quequén Grande, Buenos Aires, Argentina, is analized. The high percentage of vertical articulated individuals with ligament preserved is the result of in situ preservation. No evidences of abrasion were observed; high fragmentation percentages, both in horizontal articulated fossils and single val ves, can be attributed to bioturbation and predation. The individuals in living position were preferentially oriented suggesting the occurrence of dominant palaeocurrents. The size distribution of individuals in living position shows an almost complete absence of small specimens as a result of a higher taphonomic loss by bioturbations and/or selective predation of small sizes. The high densities of T. plebeius may indicate the superposition of different generations or populations and cannot be attributed to mas s mortality. The concentrations are interpreted as the result of a gradually changing environment as well as of other biological factors such as predation and bioturbation.